PEMBERDAYAAN DAN PENGUATAN MASYARAKAT DI WILAYAH TERTINGGAL DI KABUPATEN MELAWI MELALUI PROGRAM DMH (DESA MANDIRI HULU) TERINTEGRASI BERBASIS KEARIFAN LOKAL - Arif Didik Kurniawan; - Rachimi (Jurnal Buletin Al-Ribaath, 2017)
Nanga Ella Hilir is an underdeveloped and isolated village located in Melawi Regency, Kalimantan Barat. Consequently, supports in terms of economy, agriculture, education and health are needed to develop its potentials. Hence the programs involving students from University of Muhammadiyah Pontianak had been performed to promote development on that area becoming independent village. The programs included socialization and mentoring which focused on community empowerment activities in the fields of economy, education, fisheries and health. In the field of economy, koperasi management training, product processing, packaging and sales trainings was successfully taken place. In health sector, public health was promoted covering habitual healthy living, environmental sanitation, healthy latrines and water filtration. In fishery, village residents were trained to cultivate kinds of freshwater fish, install a tarpaulin pond and manufacture of fish feed. In the field of Education, local villagers were taught as apprentice to eradicate illiteracy. The programs also intended to enrich preschool teacher skills by creating APE instructional media. All programs had been successfully conducted and supervised directly by the head of the village. Students made substantial contribution for successful program implementation. Keywords: Independent Village, Community Empowerment